Functional Voice Assessment and Therapy Methods Supported by Telepractice, VoiceEvalU8, and Estill Voice Training - Grillo, Elizabeth U. (Seminars in Speech and Language, 2021)
Functional assessment and therapy methods are necessary for a client-centered approach that addresses the client's vocal needs across all environments. The purpose of this article is to present the approach with the intent to encourage discussion and implementation among educators, clinicians, researchers, and students. The functional approach is defined and its importance is described within the context of the World Health Organization's International Classification of Functioning, Disability, and Health with support provided by synchronous and asynchronous telepractice, the VoiceEvalU8 app, server, and web portal, and a framework that defines voice qualities (e.g., resonance, twang, loud, and others) by the anatomy and physiology of the voice production system (i.e., Estill Figures for Voice). Case scenarios are presented to highlight application of the functional voice approach.
Keywords: voice; voice disorders; function; telepractice; app technology; Estill Voice Training